(untitled) (Revista Brasileira de Plantas Medicinais, 2000)
Methanolic leaf infusion of J. pectoralis and J. gendarussa was comparatively investigated for the presence of substances that could account for their popular uses as analgesics or anti-inflammatories. The infusions are distinguished by the presence of coumarins (1,2-benzopirone and umbelliferone), O-glycosides (quercetin and kaempferol) and stigmasterol in J. pectoralis, flavonoids C- glycosides, simiarenol and α-amyrina were identified only in J. gendarussa. The data suggest that the phytotheraputic properties attributed popularly those species may be induced by different active components, possibly coumarins and flavonoids C-glycosides due to their respective predominance in the foliar infusions of J. pectoralis and J. gendarussa.